Impact of Fractal Features on Gas Adsorption and Desorption Capacities and Ad-/Desorption Hysteresis in Coals Based on Synchrotron Radiation SAXS - Zhao, Yixin; Han, Chujian; Sun, Yingfeng; Gao, Yirui; Qiao, Haiqing; Tai, Zhenyu (Frontiers in Earth Science, 2022)
Gas adsorption and desorption capacities and ad-/desorption hysteresis in coal are important for carbon capture and storage (CCS) and coalbed methane (CBM) development. To investigate the impact of fractal features on gas adsorption and desorption capacities and ad-/desorption hysteresis in coals, five coal samples were collected and carried out methane (CH4) and CO2 isothermal ad-/desorption experiments. Small angle X-ray scattering (SAXS) was applied to characterize the fractal features of coal pore structure. Results show that five coal samples show surface fractal features, represented by surface fractal dimension (Ds). The adsorption and desorption capacities of CO2 are stronger than those of CH4. In the adsorption stage, Ds and Langmuir adsorption volume (VL-ad) show a positive relationship for CH4 and CO2, due to the wan der Waals force and available adsorption sites. In the desorption stage, Ds and Langmuir desorption volume (VL-de) show a positive relationship for CH4 and CO2, because most adsorbed gas molecules can desorb and diffuse out of the pores when gas pressure decreases. No obvious correlation was found between Ds and Langmuir adsorption pressure (PL-ad) as well as between Ds and Langmuir desorption pressure (PL-de) for CO2 and CH4. An improved hysteresis index (IHI) was adopted to characterize the degree of gas ad-/desorption hysteresis. The IHI values of CO2 vary from 12.2% to 35.2%, and those of CH4 vary from 8.9% to 50.3%. The curves of Ds vs IHI for CO2 and CH4 are like an irreversible “V” shape, which yields to be further studied. This work further extends SAXS application in exploring the impact of coal pore structure on gas adsorption related phenomena, which is beneficial for CCS technology and CBM development.